2021
DOI: 10.1002/aic.17423
|View full text |Cite
|
Sign up to set email alerts
|

Methane hydrate production using a novel spiral‐agitated reactor: Promotion of hydrate formation kinetics

Abstract: To enhance hydrate formation kinetics, we presented a novel spiral‐agitated reactor, where hydrates were synthetized in pure water systems, and fast hydrate kinetics was observed under extremely mild conditions. Hydrates can nucleate within 4 min under 3.5 MPa and 275.15 K at a rotating speed of 60 rpm, and large water‐to‐hydrate conversion (>85%) was obtained at a moderate condition of 4.85 MPa, 275.15 K, and 30 rpm with an average methane uptake of 139.78 V/V, demonstrating that pure water systems are feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Therefore, fast growth of hydrates under mild conditions suggests the premise to realize the industrial application of hydrate‐based SNG technologies, while considerable gas storage should also be available. Keep this in mind, we proposed a novel spiral‐agitated reactor recently, and it was found that spiral agitation can induce fast hydrate nucleation even under extremely mild conditions 40 . In this work, hydrate formation kinetics in the spiral‐agitated reactor was further evaluated, and exciting findings were obtained.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, fast growth of hydrates under mild conditions suggests the premise to realize the industrial application of hydrate‐based SNG technologies, while considerable gas storage should also be available. Keep this in mind, we proposed a novel spiral‐agitated reactor recently, and it was found that spiral agitation can induce fast hydrate nucleation even under extremely mild conditions 40 . In this work, hydrate formation kinetics in the spiral‐agitated reactor was further evaluated, and exciting findings were obtained.…”
Section: Introductionmentioning
confidence: 94%
“…Keep this in mind, we proposed a novel spiral-agitated reactor recently, and it was found that spiral agitation can induce fast hydrate nucleation even under extremely mild conditions. 40 In this work, hydrate formation kinetics in the spiralagitated reactor was further evaluated, and exciting findings were obtained. The promotion of spiral agitation on hydrate formation was first investigated in pure water, and enhanced hydrate formation was observed under low revolving speeds.…”
Section: Introductionmentioning
confidence: 99%
“…A novel spiral-agitated reactor was used, the schematic diagram of which is presented in Figure S1, and more details can be found in our previous publications 24,35 . The high-pressure reactor is composed of a stainless-steel cylinder and a stirring rod, and the effective volume of the reactor is 581.71 mL.…”
Section: Methane Hydrate Formationmentioning
confidence: 99%
“…The storage capacity is close to 70 V/V at 3.8 MPa, while it goes up to 139.54 V/V and 144.54 V/V at 5 MPa for the inclined angle of 35°and 45°, respectively, and water-to-hydrate conversion is more than 85%. Besides, it is worth noting that the convection 35 of liquid phase inner the spiral-agitated reactor intensifies with the increase in the inclined angle, so the mass transfer between gas and liquid is enhanced at large inclined angle, leading to the increase in conversion, but when the driving force was feeble, this effect was inconspicuous.…”
Section: Enhanced Hydrate Formationmentioning
confidence: 99%
See 1 more Smart Citation